2020
DOI: 10.1371/journal.pone.0236022
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute malnutrition in children admitted in an Intensive Therapeutic and Feeding Centre of South Kivu, Eastern Democratic Republic of Congo: Why do our patients die?

Abstract: Background Severe acute malnutrition (SAM) remains a serious public health concern in low-and middle-income countries. Little is known about treatment outcomes of child inpatients in Intensive Therapeutic and Feeding Units. This study aimed to assess treatment outcomes of SAM and identify factors associated with mortality among children treated at Saint Joseph Nutritional Center, South Kivu, Eastern Democratic Republic of Congo. Methods A retrospective hospital-based cross-sectional study was conducted on medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The predictive effect of breastfeeding on mortality among children with SAM has been reported in several sub-Saharan studies [29,24]. In a study done in Ethiopia, the ndings showed that hospitalized children with SAM who were breastfed were 59% less likely to die compared to non-breastfed children (AHR: 0.41 (95% CI: 0.29-2.37)) [24].…”
Section: Discussionmentioning
confidence: 82%
“…The predictive effect of breastfeeding on mortality among children with SAM has been reported in several sub-Saharan studies [29,24]. In a study done in Ethiopia, the ndings showed that hospitalized children with SAM who were breastfed were 59% less likely to die compared to non-breastfed children (AHR: 0.41 (95% CI: 0.29-2.37)) [24].…”
Section: Discussionmentioning
confidence: 82%
“…The observed level of achievement of weight gain among children with complicated SAM is in line with reports from studies conducted in Ethiopian towns of Aksum, 18 Mekelle, 19 Woldia 20 and Gedeo. 21 Studies in India, 22 Bangladesh 15 , and Democratic Republic of Congo 14 also reported comparable levels of achievement of weight gain among children with complicated SAM. In contrast, higher proportion of treated patients achieved adequate weight gain in this study when compared with other studies conducted in the Dadaab refugee camp of Kenya 23 and Jimma university referral hospital of Ethiopia.…”
Section: Discussionmentioning
confidence: 88%
“…8 Studies on the adequacy of weight gain and associated factors among admitted children with complicated SAM were mainly conducted in non-refugee settings and outside of Africa, primarily in Asian countries. [14][15][16] According to a study in Bangladesh, admitted children with complicated SAM achieved a mean weight gain of 10.6 g/kg per day. 15 In India, 57.4% of the total 300 children did not gain final target weight despite giving adequate diet.…”
Section: Introductionmentioning
confidence: 99%
“…This is indicative of the frequent association between malnutrition and HIV in sub-Saharan African countries. The HIV rate among malnourished children is 23% in Malawi [ 49 ], while a study conducted in the Pediatric ward of the Provincial Hospital of South Kivu shows that HIV is the main infectious cause of death among children hospitalized for malnutrition [ 50 ]. However, the two HIV-positive cases in the exposed group did not have thinness or edema.…”
Section: Discussionmentioning
confidence: 99%